Contextual Fear Conditioning and Fear Generalization in Individuals With Panic Attacks - Neueder, Dorothea; Andreatta, Marta; Pauli, Paul (Frontiers in Behavioral Neuroscience, 2019)
Context conditioning characterized by unpredictable threat and its generalization may constitute risk factors for panic disorder (PD). Therefore, we examined differences between individuals with panic attacks (PA; N=21) and healthy controls (HC, N=22) in contextual learning and context generalization using a virtual reality paradigm. Successful context conditioning was indicated in both groups by higher arousal, anxiety and contingency ratings, and increased startle responses and skin conductance levels in an anxiety context (CTX+) where an aversive unconditioned stimulus occurred unpredictability versus a safety context (CTX-). PA compared to HC exhibited heightened contextual discrimination and overgeneralization of contextual anxiety on an evaluative verbal level, but not on a physiological level. We conclude that heightened context discrimination and generalization may constitute risk factors for PD or agoraphobia contributing to the characteristic avoidance of anxiety contexts and withdrawal to safety contexts and that evaluative cognitive process may play a major role.